OPTIMALISASI PEMBIAYAAN SEKTOR PERTANIAN MELAUI APLIKASI AKAD MUZARA’AH PADA PERBANKAN SYARIAH (JASEP, 2016)
Islamic banking should give a solution in lending capital in the agricultural sector through a muzara'ah scheme given the established goals of Islamic banks is for the welfare of mankind. This article aims to know the law, cooperation model muzara'ah. and will discuss how the application of such cards in the economy moder. Muzaraah in the agricultural sector is very important to be applied in Islamic banking as a superior product Indonesian Islamic bank as a real form of economic jurisprudence of Islam are beneficial for society because the agricultural sector is a sector that can absorb large kerjayang and very influential in food commodity and world economy.